An applied methodology for multi-objective optimum sizing of hybrid electric vehicle components - Eren, Yavuz; Gorgun, Haluk (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
In recent years, automobile industry focuses on the reducing the imperfections of hybrid electric vehicles (HEVs), such as higher cost, added weight of batteries, limited range, recharging facilities and emission rates. In the view of the related studies, we can infer that fuel cell (FC-Battery hybrid configuration is a viable alternative solution. Such that, FCs are eco-friendly and proper for long ranged drives, on the other hand batteries have fast response for varying power demands. Moreover, FC-Battery hybrid electric vehicle (FCBHEV) proposes solutions for the imperfections. So, we deal with optimal sizing of FCBHEV and propose a methodology for the optimization of HEV components using the multi-objective approach considering the minimization of operating cost, weight and volume simultaneously. To optimize the sizing of HEV components, the mixed integer linear programming (MILP) model is tested in GAMS v.24.1.3 using the solver CPLEX v.12 and optimization processes are performed for different range of drive cycles and the results are discussed to reveal the effectiveness of the approach. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Fuel cells; Hybrid electric vehicles; Mixed integer linear programming; Multi-objective framework; Sizing; FUEL-CELL; OPTIMIZATION; MANAGEMENT; BATTERY; DEMAND; Chemistry; Electrochemistry; Energy & Fuels